Harvard business review on greening your business profitably (Boston, 2011)
This collection of HBR articles will help you: Craft strategy to compete on green turf, Redesign your business model, products, and processes to achieve green goals
Keywords: Trách nhiệm xã hội của doanh nghiệp,Social responsibility of business,Kinh doanh doanh nghiệp,Business enterprises; Khía cạnh môi trường,Environmental aspects